PEMBUATAN ARANG AKTIF DARI SERBUK GERGAJI SENGON UNTUK PENJERNIH AIR - Gustan Pari (Jurnal Penelitian Hasil Hutan, 1992)
Experimental  study  on Paraserianthes falcataria sawdust  to produce activated  charcoal for water  treatment  is reported in this paper.  The purpose  of this  research   is to study  the effect of raw material  treatment  and  chemical addition on the activated charcoal yield and quality.The result shows that the yield of activated charcoal range from 22.88 - 35.98 %, moisture content from 1.43 - 5.85%, volatile matter from 9.16 - 15.39 %, fixed carbon from 60,90 - 75.33 %,.ash  content from 15.51 - 23.71 % and silica from 8.89-  13.69%.The adsorptive capacity of iodine, benzene and sulfuric acid respectively range from 444.26 -  761.40 mg/g, 1.23 - 8.83 % and 17.40 -35.26 %. Good quality of the activated charcoal was produced from charcoal of sengon sawdust with sodium  carbonate as activator. This is especially  for the adsorptive capacity of iodine where this criteria has met the commercial standard requirement  of the Americoal  Water Work Association and the Indonesian Industrial Standard.The quality of water after treatment with the activated charcoal shows that the iron (Fe) content range from 0.00 - 0.09mg/1,  calsium  (Ca) from  3.35 - 22.66 mg/1,  sodium  (Na) from 8.80 -  9340.0mg/1,  mangan  (Mn) from  0.00 - 0.08mg/1,  nicel (Ni) from  0.03 -  0.77mg/1,  chloride (Cl) from 21.0 -  170.0mg/1,  ammonium  (NH4) from  0.00 - 0.44 mg / 1  and chemical oxygen demand (COD) range from 21.40 - 61.20 mg / 1